Localisation of Ca and HMFG2 antigens in breast tissue by immunoperoxidase, immunofluorescence, and immunoelectron microscopy. Issue 5 (May 1985) - Beckford, U; Barbatis, C; Beesley, J E; Linsell, J C; Chantler, S M
Abstract : The reactivities of Ca1 and HMFG2 monoclonal antibodies were compared on paraffin wax embedded breast tissues using indirect immunoperoxidase. The expression of Ca antigen, like HMFG2, is not exclusive to malignancy: Ca was present in 41/53 (77%) and HMFG2 in 42/53 (79.2%) non-malignant conditions and both were present in 33/35 (94%) carcinomas. Similar results were obtained when cryostat sections were used. Both antigens showed striking similarities in their topographical distributions, although quantitative differences were seen. Their cellular and sub-cellular localisations were investigated by double labelling immunofluorescence and immunogold electron microscopy, which showed that the expression of Ca and HMFG2 antigens was closely associated on cell membranes but that the epitopes were distinct.